EXOSC5 as a Novel Prognostic Marker Promotes Proliferation of Colorectal Cancer via Activating the ERK and AKT Pathways - Pan, Hongda; Pan, Jingxin; Song, Shibo; Ji, Lei; Lv, Hong; Yang, Zhangru (Frontiers in Oncology, 2019)
Background and Objective: Exosome component 5 (EXOSC5) is a novel cancer-related gene that is aberrantly expressed in various malignances. However, the role and mechanism of EXOSC5 have not been explored in colorectal cancer (CRC). In this study, we investigated the functions and mechanisms by which EXOSC5 promotes the progression of CRC. Methods: EXOSC5 expressions in paired CRC and adjacent normal tissues and CRC cell lines were examined via quantitative real-time PCR (qRT-PCR), Western blot and immunohistochemistry (IHC). In vitro experiments including Cell Counting Kit-8 (CCK-8), colony formation and flow cytometry were used to explore the effects of EXOSC5 on cell proliferation of CRC. Subcutaneous tumorigenesis was conducted in mice to explore the effects of EXOSC5 in vivo. The impacts of EXOSC5 on ERK and Akt signaling pathways were measured by Western blot. Results: The mRNA and protein expressions of EXOSC5 were up-regulated in CRC compared with adjacent normal tissues. IHC analysis indicated that high EXOSC5 level was positively associated with poor prognosis. EXOSC5 overexpression facilitated the growth of CRC cells, whereas the knockdown of EXOSC5 resulted in decreased proliferation, G1/S phase transition arrest and apoptosis. Activation of the ERK and Akt pathways was involved in the oncogenic functions of EXOSC5 in CRC. Conclusion: EXOSC5 is upregulated in CRC and plays a tumor promoting role partly through activation of ERK and Akt signaling pathways. Accordingly, EXOSC5 acts as a novel oncogene and may be a prognostic factor or therapeutic target for CRC.